2021
DOI: 10.3389/fcimb.2021.689770
|View full text |Cite
|
Sign up to set email alerts
|

Phage vB_PaeS-PAJD-1 Rescues Murine Mastitis Infected With Multidrug-Resistant Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a Gram-negative pathogen that causes a variety of infections in humans and animals. Due to the inappropriate use of antibiotics, multi-drug resistant (MDR) P. aeruginosa strains have emerged and are prevailing. In recent years, cow mastitis caused by MDR P. aeruginosa has attracted attention. In this study, a microbial community analysis revealed that P. aeruginosa could be a cause of pathogen-induced cow mastitis. Five MDR P. aeruginosa strains were isolated from milk diagnosed as ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…A BLASTN search of the entire PIP sequence revealed that it had the highest sequence identity to the Nipunavirus Pseudomonas phage vB_PaeS_PAJD-1, a phage put forth as a candidate for phage therapy against P. aeruginosa mastitis infection ( 11 ). Similarity analysis showed that PIP had a percent identity of 80.35% and a query cover of 91% when compared to phage vB_PaeS_PAJD-1.…”
Section: Observationmentioning
confidence: 99%
“…A BLASTN search of the entire PIP sequence revealed that it had the highest sequence identity to the Nipunavirus Pseudomonas phage vB_PaeS_PAJD-1, a phage put forth as a candidate for phage therapy against P. aeruginosa mastitis infection ( 11 ). Similarity analysis showed that PIP had a percent identity of 80.35% and a query cover of 91% when compared to phage vB_PaeS_PAJD-1.…”
Section: Observationmentioning
confidence: 99%
“…Sequel to successful adsorption and penetration, lytic phages immediately hijack their host DNA replication machinery to synthetise genetic materials and structural proteins during the latent period. The time taken to achieve this has been reported to vary in bovine mastitis phages and could range from 10 ( S. aureus) , 15 ( E. faecum ), 20 ( P. aeruginosa phage), to 30 min ( S. agalactiae ) [ 7 , 50 , 67 , 69 ]. Subsequently, after viral synthesis, numerous phage particles are assembled and eventually released by the lysis of the host through a combined activity of the endolysin and holin enzymes that degrade the bacteria cell wall [ 75 ].…”
Section: The Case For Phage Therapy To Control Bovine Mastitismentioning
confidence: 99%
“…Subsequently, after viral synthesis, numerous phage particles are assembled and eventually released by the lysis of the host through a combined activity of the endolysin and holin enzymes that degrade the bacteria cell wall [ 75 ]. For bovine mastitis, phage progeny or burst (number of phage particles synthesised and released per single bacterial cell) varies from 20 to 100 PFU/cell within ~175 min [ 7 , 27 , 50 , 67 , 69 ]. The ability of lytic phages to ultimately lyse infected bacteria and amplify after infection ensures the clearance of the bacterial pathogens as well as continual increased supply of infective phages (auto-dosing) at infection sites [ 26 , 71 ].…”
Section: The Case For Phage Therapy To Control Bovine Mastitismentioning
confidence: 99%
“…The T4 phage vB_EcoM-UFV13, a novel E. coli phage with a broad host range, decreased the bacterial load by 90% in murine mammary glands and had a positive result on E. coli -induced mastitis in dairy cows ( 104 ). PAJD-1, a phage isolated from sewage samples on a dairy farm, lysed 80% of P. aeruginosa strains ( 105 ). The edema and hemorrhagic response of mouse mammary tissues caused by P. aeruginosa was greatly alleviated by the action of PAJD-1 in vivo , similar to antibiotics ( 105 ).…”
Section: Bacteriophagesmentioning
confidence: 99%